2011
DOI: 10.1074/jbc.m111.276683
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible Factor-1α Protein Negatively Regulates Load-induced Bone Formation

Abstract: Background:The mechanisms by which bone responds to changes in its loading environment are poorly understood. Results: Mechanical signals induce Hif-1␣ expression, and mice lacking Hif-1␣ in bone are more responsive to loading. Conclusion: Hif-1␣ is a novel regulator of skeletal mechanotransduction that impinges on Wnt signaling. Significance: Understanding skeletal mechanotransduction may lead to the development of therapies designed to enhance bone formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 57 publications
4
39
0
Order By: Relevance
“…When challenged with non-damaging forelimb compression, ΔHIF-1α mice respond normally, resulting in a greater absolute level of bone formation in ΔHIF-1α loaded limbs compared to WT. This finding is similar to results from a previous study that showed ΔHIF-1α mice generated more bone following 3 weeks of tibial bending than WT mice, although they found no differences in bone formation in sham limbs [21]. The increased bone formation in non-loaded limbs observed in this study is consistent with the age-related changes in bone size previously reported – ΔHIF-1α mice begin life with small bones that become comparable to their wild type littermates in adulthood [21].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…When challenged with non-damaging forelimb compression, ΔHIF-1α mice respond normally, resulting in a greater absolute level of bone formation in ΔHIF-1α loaded limbs compared to WT. This finding is similar to results from a previous study that showed ΔHIF-1α mice generated more bone following 3 weeks of tibial bending than WT mice, although they found no differences in bone formation in sham limbs [21]. The increased bone formation in non-loaded limbs observed in this study is consistent with the age-related changes in bone size previously reported – ΔHIF-1α mice begin life with small bones that become comparable to their wild type littermates in adulthood [21].…”
Section: Discussionsupporting
confidence: 91%
“…Female mice were housed under standard conditions until 18–22 weeks of age, to ensure skeletal maturity [31, 32] and allow approximate normalization of any cortical bone phenotype [21]. At the time of loading, there was no significant difference in weight between WT (23.1 ± 1.4 g) and ΔHIF-1α (22.6 ± 2.0 g) mice.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown that reactivation of HIF-1a in ost-MSCs effectively inhibits OxPhos to the levels found in undifferentiated cells. Earlier works provide opposing views on the role of HIF-1 in osteoblasts; while Regan et al describe an anabolic effect of HIF-1 [22], Riddle et al report an inhibitory role of HIF-1 on osteoblast differentiation [23]. Our data provide insight on this controversy: HIF-1a may be required at early stages of osteogenesis to maintain active glycolysis needed for high rates of proliferation.…”
Section: Discussionmentioning
confidence: 57%